Bacillus Species’ Gaseous Metabolites Prolong the Shelf Life of Apples and Grapes - Shen, Hongyi (International Journal of Natural Resources and Environmental Studies, 2024)
In view of the threat to the environment posed by the widely used plant and fruit preservation chemicals in current agricultural practices, and the indispensability of fruit and plant preservatives in ensuring the yield of agricultural products, it is urgent to explore environmentally friendly and efficient preservative alternatives. Against this backdrop, bacterial preservatives stand out as a potential green solution. In this study, 12 strains of Bacillus derived from different ecological niches were carefully screened to evaluate the inhibitory efficacy of their gaseous metabolites against Anthracnose colloidospora, a common fruit pathogen, by bisectional method. The results showed that the bacterial suspension of strain B4 was the most prominent in inhibiting the growth of Colloidosporum anthracnose, and it significantly narrowed the growth circle of pathogenic bacteria, so it was selected as the object for further optimization and application. Subsequently, we designed a practical application test for fruit preservation, in which the bacteria of strain B4 were directly placed in the same environment as the fruit to be preserved, and the observation was continued for five days. By comparing and analyzing the fruit state before and after treatment, we were pleased to find that strain B4 showed a positive effect on inhibiting fruit rot, indicating its great potential as a natural fruit preservative. This discovery not only provides a scientific basis for reducing the use of chemical preservatives, but also contributes to the sustainable development of agriculture and the protection of the ecological environment.